2021
DOI: 10.1111/and.14052
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine increased progressive motility of human spermatozoa in normozoospermic and asthenozoospermic semen samples and enhanced activity of seminal creatine kinase

Abstract: Even though the effect of caffeine on humans' health has been revealed in various research studies, its effect on semen quality has yet to be well explained. Here, we measured the effect of caffeine at 1, 5, 10 and 20 mM on motility of human spermatozoa in normozoospermic and asthenozoospermic semen samples, level of seminal nitric oxide, chelation of seminal calcium ions and activity of seminal creatine kinase. Fifty‐one normozoospermic and ten asthenozoospermic semen samples were recruited in this study. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In andrology research, progressively motile sperm is considered the most sensitive semen quality parameters to evaluate the effect of given exogenous factors (e.g., drugs) (Banihani & Khaled, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In andrology research, progressively motile sperm is considered the most sensitive semen quality parameters to evaluate the effect of given exogenous factors (e.g., drugs) (Banihani & Khaled, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In andrology research, progressively motile sperm is considered the most sensitive semen quality parameters to evaluate the effect of given exogenous factors (e.g., drugs) (Banihani & Khaled, 2021). Therefore, in this study, we intended to measure the in vitro hierarchy of ranitidine drug at a range of concentrations on progressive motility of sperm.…”
Section: Resultsmentioning
confidence: 99%
“…Also, if the energy source is insufficient, motility will drop again. For instance, a previous study demonstrates that 10 nM of caffeine significantly increased the progressive motility of spermatozoa in normozoospermic and asthenozoospermic groups [49]. Studies have also shown that the caffeine content in tea increases with increasing steep time and temperature [50][51][52].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in the present study, we observed that the recovery rates in the inner tube were reduced to less than one‐fifth (~20%), although sufficient sperm numbers were recovered for IVF. It has been demonstrated that, in normal human sperm and azoospermia, the presence of 10 mM caffeine increases motility, whereas 0, 1, and 5 mM caffeine cause no statistical change (Banihani & Khaled, 2021). In the present study, using frozen–thawed porcine sperm, the addition of more than 5 mM caffeine increased the recovery rate; however, the addition of 10 mM caffeine decreased sperm quality, including motility.…”
Section: Discussionmentioning
confidence: 99%